2012
DOI: 10.1299/jtst.7.227
|View full text |Cite
|
Sign up to set email alerts
|

Application of Infrared Thermography as a Diagnostic Tool of Knee Osteoarthritis

Abstract: This paper aimed to study the feasibility of application of infrared thermography to detect osteoarthritis of the knee and to compare the distribution of skin temperature between participants with osteoarthritis and those without pathology. All tests were conducted at LACM (Laboratory of Mechanical Stresses Analysis) and the gymnasium of the University of Reims Champagne Ardennes. IR thermography was performed using an IR camera. Ten participants with knee osteoarthritis and 12 reference healthy participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…However, the author of this study evaluated pain by questionnaires (Knee Pain Scale and WOMAC pain subscale) [17]. As the mechanisms of pain in OA are still not fully established and understood [3,4], precise methods such as ther mography and the objective evaluation of pain through pressure pain thresholds (a technique already employed by previous studies) [18,19] can bring information about the relationship between pain and cutaneous tempera ture in this disease. Although thermography is a reli able diagnostic tool to detect quantifiable cutaneous temperature patterns in patients with OA [18], a recent study highlights the fact that current scientific literature is still scarce about the employment of this technique in OA [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the author of this study evaluated pain by questionnaires (Knee Pain Scale and WOMAC pain subscale) [17]. As the mechanisms of pain in OA are still not fully established and understood [3,4], precise methods such as ther mography and the objective evaluation of pain through pressure pain thresholds (a technique already employed by previous studies) [18,19] can bring information about the relationship between pain and cutaneous tempera ture in this disease. Although thermography is a reli able diagnostic tool to detect quantifiable cutaneous temperature patterns in patients with OA [18], a recent study highlights the fact that current scientific literature is still scarce about the employment of this technique in OA [19].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the significant values of sensitivity and specificity the method seems to have great potential for knee osteoarthritis screening. Arfaoui et al [23] investigated the correlation between knee skin temperature and the pain intensity among patients with osteoarthritis (10 patients with unilateral knee osteoarthritis) and without pathology (12 patients). TII of the right and left knees was performed to record skin temperature with CEDIP Titanium HD560M IR camera in the (3.5-5) lm wavelength range.…”
Section: Diagnosis Of Knee Osteoarthritismentioning
confidence: 99%
“…For example, Fokam and Lehmann [26] mentioned that IRT is a reliable tool for pain assessment in inflammatory arthritis due to the correlation between skin temperature and arthritis pain. Likewise, other studies have found an association between the temperature of the patellar region (i.e., a sign of inflammation) and the severity of osteoarthrosis in the knee [27,28]. Based on this assumption, Jin et al [29] proposed an automatic analysis method for thermographic images of the knee (specifically in the center of the patella) for osteoarthrosis screening based on a Support Vector Machine.…”
Section: Introductionmentioning
confidence: 96%